The traitor's game - Nielsen, Jennifer A. (Nielsen, Jennifer A. Traitor's game, 2019)
In the kingdom of Antora, sixteen-year-old Kestra Dallisor is returning from exile and traveling home to meet her father, chief counsel to the evil ruler Lord Endrick. A group of rebels kidnap Kestra and plan to force her to retrieve the lost Olden Blade, the only object that can destroy Lord Endrick. Kestra fights back by any means necessary, giving one of her kidnappers, Simon, all he can handle. However, as long-buried secrets come to light, Kestra questions everything she's been told about her family and her kingdom.